2020
DOI: 10.3390/metabo10090374
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling in Neuromyelitis Optica Spectrum Disorder Biomarker Discovery

Abstract: There is no specific test for diagnosing neuromyelitis optica spectrum disorder (NMOSD), a disabling autoimmune disease of the central nervous system. Instead, diagnosis relies on ruling out other related disorders with overlapping clinical symptoms. An urgency for NMOSD biomarker discovery is underscored by adverse responses to treatment following misdiagnosis and poor prognosis following the delayed onset of treatment. Pathogenic autoantibiotics that target the water channel aquaporin-4 (AQP4) and myelin oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 219 publications
(366 reference statements)
0
5
0
Order By: Relevance
“…Previous metabolomic studies have shown an association between a disturbance of amino acid metabolism and autoimmune disease and a certain amino acid profile might have a diagnostic potential ( Fernández-Ochoa et al, 2019 ; Thoman and McKarns, 2020 ; Yan et al, 2020 ). Similarly, we found that amino acids were differentially expressed in urine from VKH patients and they were the most abundant differential metabolites in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous metabolomic studies have shown an association between a disturbance of amino acid metabolism and autoimmune disease and a certain amino acid profile might have a diagnostic potential ( Fernández-Ochoa et al, 2019 ; Thoman and McKarns, 2020 ; Yan et al, 2020 ). Similarly, we found that amino acids were differentially expressed in urine from VKH patients and they were the most abundant differential metabolites in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…With the backing of mass spectrometry and bioinformatics technologies, a highresolution and high-accuracy proteomics technique has been established to identify new MS and NMOSD biomarkers [11,12] in CSF [13][14][15][16][17], sera [18], and urine [19]. These investigations demonstrate the considerable diagnostic potential of this approach in clinical diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to blood biomarkers, biomarkers from urine, feces and cerebrospinal fluid can be used to identify diseases. One such biomarker in the spinal fluid is myelin oligodendrocyte glycoprotein (MOG-IgG) and aquaporin-4 (AQP4), which are used to identify neuromyelitis optica spectrum disorders (30). In the field of ophthalmology, imaging findings and artificial intelligence analysis have been used as biomarkers for prediction and therapy response of choroidal diseases (31)(32)(33), and intraretinal cysts can be used for the prognosis of neovascular age-related macular (AMD) disease (34).…”
Section: Introductionmentioning
confidence: 99%